Personal Information Disclosure Strategies of Cyberbullying Victims to the Family - Ismi, Maya Faridatul; Aisyah, Vinisa Nurul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Cyberbullying is aggressive and repetitive behavior perpetrated using digital technology to scare, anger or embarrass someone. Victims of cyberbullying often experience negative impacts on their mental health, self-confidence and social relationships. One strategy or way to cope with their problems is to disclose to their family. Self-disclosure is not always easy due to considerations about privacy and the risks involved. Victims of cyberbullying are not always open in sharing their feelings and the bullying incidents they receive. This study aims to find out how the strategy of disclosing personal information of cyberbullying victims to families. This study uses the Communication Privacy Management theory proposed by Petronio to analyze how cyberbullying victims can determine the boundaries of their privacy and the rules used to disclose or hide their personal information. The research conducted used qualitative methods and used a descriptive approach. The sampling technique in this study was to use the snowball sampling method. The data collected using interview techniques with four informants who have experienced cyberbullying, researchers used interview techniques for this study conducted with semi-structured interviews. Researchers use source triangulation which is used as a data collection technique in research. The data analysis technique used in this research is the analysis of the Miles and Huberman model, the analysis is carried out during data collection and after completion of data collection within a certain period. The results showed that cyberbullying victims have different privacy boundaries. This study also found that victims of cyberbullying have certain rules used to disclose or hide their personal information to their family such as the level of trust and expectations and responses.